Influence of motor skills' training methodic on senior pupils' speed-power and endurance qualities at light athletic trainings with aplication of interdisciplinary connections - Abdel Baset Al-Ravashdeh; Zh.L. Kozina; T.A. Bazilyuk; A.S. Ilnickaya (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to determine influence of technology of integral motor and intellectual aspects' impact on development of senior pupils' motor skills. Material: in the research 2 groups of pupils participated: control (n=34 - boys) and experimental (n=34 - boys). Results: confident changes in light athletic skills have been registered. In experimental group confident changes in indicators of motor fitness were registered in tests for speed-power qualities and endurance (short and long distance run, jumps, throws). We also found that it is necessary to take into account dozing of exercises, when training motor actions. Conclusions: it is recommended to use approaches to creation of holistic idea of movement. Theoretical part shall be oriented on deep understanding of physical principles of movements' rational technique. Keywords: abilities, skills, athletics, students, methods.